Acetylation of the CspA family protein CspC controls the type III secretion system through translational regulation of exsA in Pseudomonas aeruginosa. Issue 12 (17th June 2021) - Li, Shouyi; Weng, Yuding; Li, Xiaoxiao; Yue, Zhuo; Chai, Zhouyi; Zhang, Xinxin; Gong, Xuetao; Pan, Xiaolei; Jin, Yongxin; Bai, Fang; Cheng, Zhihui; Wu, Weihui
Abstract: The ability to fine tune global gene expression in response to host environment is critical for the virulence of pathogenic bacteria. The host temperature is exploited by the bacteria as a cue for triggering virulence gene expression. However, little is known about the mechanism employed by Pseudomonas aeruginosa to response to host body temperature. CspA family proteins are RNA chaperones that modulate gene expression. Here we explored the functions of P. aeruginosa CspA family proteins and found that CspC (PA0456) controls the bacterial virulence. Combining transcriptomic analyses, RNA-immunoprecipitation and high-throughput sequencing (RIP-Seq), we demonstrated that CspC represses the type III secretion system (T3SS) by binding to the 5′ untranslated region of the mRNA of exsA, which encodes the T3SS master regulatory protein. We further demonstrated that acetylation at K41 of the CspC reduces its affinity to nucleic acids. Shifting the culture temperature from 25°C to 37°C or infection of mouse lung increased the CspC acetylation, which derepressed the expression of the T3SS genes, resulting in elevated virulence. Overall, our results identified the regulatory targets of CspC and revealed a regulatory mechanism of the T3SS in response to temperature shift and host in vivo environment.